1970
DOI: 10.1037/h0029408
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in preschool children without histories of complications of pregnancy and delivery.

Abstract: Sex differences in aggression and other behaviors were reexamined in the light of studies indicating that an unidentified contributor in past research could have been greater male vulnerability to minimal brain damage resulting from complications of pregnancy and delivery. Eleven of 27 measures obtained by direct observation or mechanical recording in free play or experimental situations showed sex differences in a sample of 30 male and 25 female preschool children screened for complications. The number of sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 30 publications
1
18
1
1
Order By: Relevance
“…In these cases no sex differences were found contrary to the results of PEDERSEN and BELL (1970) for human children and the present study on gorillas, who both observed more locomotion in males. FREEMAN and ALCOCK (1973) noted a higher frequency in nest building in female gorilla juveniles than in males, as was also found in this study in infants and juveniles.…”
Section: Discussioncontrasting
confidence: 86%
“…In these cases no sex differences were found contrary to the results of PEDERSEN and BELL (1970) for human children and the present study on gorillas, who both observed more locomotion in males. FREEMAN and ALCOCK (1973) noted a higher frequency in nest building in female gorilla juveniles than in males, as was also found in this study in infants and juveniles.…”
Section: Discussioncontrasting
confidence: 86%
“…Noteworthy in this discussion is the evidence from toy preference studies which points to early sex typing of toy choice in boys and girls. By preschool age girls sew, string beads, play at housekeeping; boys play with guns, toy trucks, tractors, blocks, fire engines and do carpentry {Clark etal., 1969, Pederson andBell, 1970). While there is a clear difference in toy preference between the sexes, there is no evidence for any relationship between these preferences or modes of play and development of visuospatial skills in adulthood.…”
Section: Influence O F Environmentmentioning
confidence: 90%
“…It is also noteworthy that girls report being more fearful and timid in uncertain situations than boys and are more cautious and take fewer risks than boys (Christopherson, 1989;Ginsburg & Miller, 1982). Girls are also more compliant than boys beginning in the toddler period and throughout childhood (Kochanska & Aksan, in press;Minton, Kagan, & Levine, 1971;Pederson & Bell, 1970;Smith & Dagliesh, 1977), and girls are more prone to anxiety disorders (Weissman, 1985).…”
Section: An Adaptationist Perspective On Conscientiousnessmentioning
confidence: 93%